LITERASI MEDIA ORANG TUA SEBAGAI UPAYA MENGATASI DAMPAK MENONTON TELEVISI ANAK DI KELURAHAN BALUWARTI SURAKARTA - Lukmin Sorela (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2021)
Television produces two sides, namely positive and negative impacts. Through discussing the implications and problems of television shows, such as the low quality of the content of the show, shows that are not by age, the negative impacts caused, and the long duration of watching television, media literacy is ideal for parents as there are problems with television for children who watch television. Television activities. The purpose of this study was to determine the form of television media literacy owned by parents to overcome the impact when children watch television and to understand the conditions of parental action to overcome the effects of children's television viewing activities based on the concept of media literacy. The results showed that (1) Every parent has media literacy through knowledge and abilities. Parents' media literacy has reached the categories and indicators specified in media literacy (2) Parents carry out various media literacy actions carried out in different ways according to their knowledge and abilities in media literacy, such as mentoring, watching television, children's rules managing television activities, choosing shows, limiting television viewing activities, and distracting children from television. Parents have motives and reasons for their media literacy actions, categorized into four categories of Max Weber social action.